Innovation in local economies. Germany in comparative context (New York, 2009)
"The study of varieties of capitalism is moving on from the analysis of static national types to embrace local and sectoral diversity and the study of systems in the process of major change. This volume addresses the issue by examining four localised sectors, comparing a German case with one in another European country. The general changes taking place in Germany itself and the other countries (Hungary, Sweden, and the UK) form the context of the studies. The case studies concern: * Furniture making in North-Rhine Westphalia and southern Sweden, * Automotive manufacture in east Germany and northern Hungary, * Biotechnology around Munich and Cambridge, * TV programme and film-making in Cologne and central London. The studies find a complex pattern of conformity with, and deviation from, national types, but only occasional examples of where divergence takes the form of a direct confrontation with a national model. This is partly because national models are themselves changing; partly because they are often capable of accommodating more diversity than is often assumed by national studies; and partly because firms are increasingly able to reach outside their national boundaries for institutional resources."